2010
DOI: 10.1007/s00702-010-0535-z
|View full text |Cite
|
Sign up to set email alerts
|

Is C-reactive protein level a marker of advanced motor and neuropsychiatric complications in Parkinson’s disease?

Abstract: C-reactive protein (CRP) is a plasma protein involved in inflammation. While its levels have been associated with stroke, cognitive impairment and depression, the association with clinical characteristics of Parkinson's disease (PD) is unknown. A total of 73 consecutive patients with PD (46 males, age 68.8 ± 11.5 years) were evaluated regarding motor as well as cognitive and psychiatric features of PD. Plasma CRP levels were determined and tests for associations with disease parameters were performed. The aver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 24 publications
1
20
1
Order By: Relevance
“…Here, they also failed to demonstrate any associations between CRP levels and motor as well as cognitive and psychiatric features such as severity of depression, psychosis, dementia, cognitive decline or frontal lobe dysfunction. CRP is an acute-phase protein whose plasma levels increase during inflammatory states [46]. In line with these findings, another study has shown the lack of significant correlation between IL-6 or CRP blood levels and any of the NMS scales, including depressive and anxiety symptom assessment [5].…”
Section: The Role Of Inflammation and Immune Responses In Cognitive Asupporting
confidence: 58%
See 2 more Smart Citations
“…Here, they also failed to demonstrate any associations between CRP levels and motor as well as cognitive and psychiatric features such as severity of depression, psychosis, dementia, cognitive decline or frontal lobe dysfunction. CRP is an acute-phase protein whose plasma levels increase during inflammatory states [46]. In line with these findings, another study has shown the lack of significant correlation between IL-6 or CRP blood levels and any of the NMS scales, including depressive and anxiety symptom assessment [5].…”
Section: The Role Of Inflammation and Immune Responses In Cognitive Asupporting
confidence: 58%
“…Also, sIL-2-R levels were able to predict FACIT-F and HAD scores even after the effects of age, gender, antiparkinsonian medications and severity of motor symptoms were controlled for [5]. One other study demonstrated that the presence of current or prior depression was more common in those PD patients who had higher CRP plasma levels [46]. …”
Section: The Role Of Inflammation and Immune Responses In Cognitive Amentioning
confidence: 99%
See 1 more Smart Citation
“…The significance of being able to block inflammation at any point during the disease might have benefits for non-motor symptoms [13, 39]. Subsequently, others have shown that TNF [16] and c-reactive protein (CRP), classic companion biomarkers of inflammation, were correlated with fatigue [15], depression [40], cognition [41], and hallucination [42] in PD patients and plasma solTNF receptors were correlated with cognitive impairment in PD patients [17]. Elevated CRP has also been observed to correlate with motor dysfunction in PD patients [4346].…”
Section: Discussionmentioning
confidence: 99%
“…As such, biomarkers could predict risk of future age-related morbidity and mortality. However, the search for these biomarkers has often failed [18,19,37]. For example, telomere length has been a highly studied ‘biomarker’ of ageing, as they shorten as individuals grow older, yet telomeres have failed as a predictor of mortality [18,19].…”
Section: Proteomics and Metabolomics As Ageing Biomarkersmentioning
confidence: 99%